King George : what was his problem? : everything your schoolbooks didn't tell you about the American Revolution - Sheinkin, Steve; Robinson, Tim, 1963- (New York : Scholastic, 2009)
This is a take on the history of the American Revolutionary War sure to fascinate readers of all ages. King George: What Was His Problem? mentions details about the war that are often left out of textbooks, but all the anecdotes are entirely true!
How to start a revolution -- A sleepless night before revolution -- Who fired the shot heard 'round the world? -- George Washington, meet your army -- Declare independence already! -- Losing and retreating in '76 -- Showdown at Saratoga -- Will we ever win this war? -- The great race to Yorktown -- What ever happened to ...?
"The whole hilarious story of the American revolution"--Cover.
Includes bibliographical references and index.
Keywords: United States -- History -- Revolution, 1775-1783 -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Anecdotes -- Juvenile literature; United States -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Anecdotes